Stakeholder Management Theory, Firm Strategy, and Ambidexterity - Minoja, Mario (Journal of business ethics, 2012)
Stakeholder theory scholars have recently addressed two crucial calls: the first is for the integration of strategy and ethics, of stakeholder theory and strategic management, and the second call is for the development of a dynamic approach to stakeholder management. I have attempted to answer these calls by developing a theoretical framework that links together stakeholder management, stakeholder commitment to cooperate with the firm, key decision makers’ ethical commitment, and firm strategy. Starting from the basic assumption that managers cannot meet all stakeholders’ demands immediately and in a tailored manner, I contend, first, that an ambidextrous approach to stakeholder management is conducive to stakeholders’ commitment to cooperate for the sustainable well-being of the firm and, second, that firm strategy and key decision makers’ ethical commitment moderate the relationship between an ambidextrous stakeholder management and stakeholder commitment to cooperate. Furthermore, drawing on this theoretical framework, I attempt to address the call for the integration of strategy and ethics by proposing a three-level conceptual model that distinguishes the objectives, the field, and the levers of integration. Finally, I outline a set of propositions that, taken together, represent a first attempt to develop a dynamic approach to stakeholder management.